Effect of variety and nitrogen on growth and yield of little millet (Panicum miliare) under dry temperate condition - SAINI, J P; THAKUR, S R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted in dry-temperate zone of district Kinnaur during summer season of 1990 and 1991,’BAU2’ little millet (Panicum miliare L.) gave significantly higher grain yield (57.5 and 42.1%) compared with ’Co2’ and ’Local’.Application of 60kg/N/ha was at par with that of 80 kgN/ha and gave signigicantly highest grain yield owing to the improved growth and yield attributes compared with the remaining N levels. There was 116.3 and 17.0% increase in yield at 60 kgN/ha compared with 0 and 40 kg/ha respectively.